Analysis of Concrete Strength with Addition of Bamboo Fiber (International Journal of Geoscience, Engineering and Technology, 2021)
Currently, technological advances and the development of new construction methods are being directed towards the search for more sustainable materials, that is, research and studies are being developed in favor of the use of materials that have low energetic consumption, that are less polluting, taht are accessible and economically viable, as well as have high mechanical performance. Bamboo is one of the materials that fits such conditions and, therefore, has been the object of study in civil construction. Therefore, the main purpose of this work is to analyze the behavior of the concrete with the addition of bamboo fibers, regarding the resistance of the material, and to compare the results obtained with conventional concrete. Three traces were performed, one for conventional concrete, one for concrete with the addition of 1% bamboo fiber and the last with the addition of 2% bamboo fiber, where the specimens were submitted to uniaxial compression and diametrical compression resistance tests on the 7th, 14th and 28th day of the concrete curing time. The results showed an increase in the tensile strength of concrete with the addition of bamboo fiber in relation to conventional concrete, in all the days in which the tests were performed, but there was little difference between the traces of conventional concrete, with 1% and 2% of fiber in relation to compressive strength.